Left testicular venous infarction secondary to large spontaneous retroperitoneal haematoma compressing left testicular vein: a case report. Issue 8 (25th August 2022) - Vu, Thomas; Lechmiannandan, Sivaneswaran; Birks, Sarah; Grummet, Jeremy
Abstract : A man in his early 50s presented with a spontaneous large left-sided retroperitoneal haematoma (RPH), on a background of therapeutic anticoagulation with warfarin for homozygous factor V Leiden. His international normalised ratio was found to be supra-therapeutic at 9.0 on presentation. He was treated non-operatively with prompt reversal of the coagulopathy and close monitoring. On day 4 of the admission, the patient reported scrotal pain and swelling. An urgent scrotal ultrasound revealed infarction of the left testis and the patient was taken to an emergency scrotal exploration. Intraoperatively, the left testis was found to be no longer viable with the left spermatic vein and venules completely thrombosed with extensive clots, while the left testicular artery remained intact. Consequently, a left orchidectomy was performed. Therapeutic anticoagulation was recommenced on day 3 postoperatively. It is thought that the large RPH caused extrinsic compression of the left testicular vein, in addition to the patient's pre-existing factor V Leiden, which resulted in thrombosis of the blood vessel.